The Influence of Work-Life Balance, Job Stress, and Work Environment on Sustainable Employee Performance: The Mediating Role of Job Satisfaction - Fransiscus Agung Dono Mulyono; M. Ali Iqbal (Indonesian Journal of Business Analytics, 2025)
This study investigates the influence of work-life balance, job stress, and work environment on sustainable employee performance among 146 train crew members at PT Kereta Api Indonesia (Persero). Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), this study examines the mediating role of job satisfaction in this relationship. The findings reveal that job stress and work environment are significant predictors of sustainable performance, while work-life balance operates indirectly. Job satisfaction emerges as a critical mediator, fully transmitting the effect of work-life balance and partially mediating the effect of job stress on performance. Specifically, job stress is the strongest negative predictor of job satisfaction. These results provide crucial managerial insights, suggesting that mitigating job stress and enhancing job satisfaction are key strategies for driving sustainable employee performance in high-risk operational roles.